Back to the future: Thoughts about development and the future of missiology - Alawode, Akinyemi O (Stellenbosch Theological Journal, 2016)
Missiologists have spent a lot of time since the 1990s in debating issues such as postmodernism, paradigm changes, etc. For the growing majority of Christians in the world (in Africa), pervasive poverty and the resultant need for community development seem to be more pressing. How and where will our people get their everyday needs? We should return to the debate of the 1970s and 1980s about the preferential option for the poor – churches, mission agencies and academics have too easily forgotten about this. Community development should therefore return to the top of the missiological agenda again. Missiologists have left development to the “experts” too easily. Faith communities and their leaders mostly know better than any others what kind of development is needed; faith communities are often the only credible and workable social institutions left in many areas; and community development is a fundamental dimension of Christian mission. There are signs that academics are beginning to be aware of this reality, so a call seems to be in order for missiologists to go “back to the future” by integrating the preferential option for the poor, the need for community development, and missiological praxis again.